2007
DOI: 10.1179/016164107x158965
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of BAX and cyclin D1 genes in patients with malignant glioma

Abstract: These findings suggest that both cyclin D1 and BAX genes alteration are rarely found in brain tumors. However, the alteration might cause a significant effect of the normal protein production and this might contribute to the development of brain tumorigenesis in Malaysian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…NF-κB has been implicated in the regulation of glioma cell proliferation through the upregulation of oncogenes, including cyclin D1, cyclin E, and c-myc (50)(51)(52)(53)(54). The present study revealed that overexpression of TMEM16A significantly increased transcription levels of these genes, which may explain why TMEM16A promotes cell proliferation in gliomas.…”
Section: A B a Bsupporting
confidence: 50%
“…NF-κB has been implicated in the regulation of glioma cell proliferation through the upregulation of oncogenes, including cyclin D1, cyclin E, and c-myc (50)(51)(52)(53)(54). The present study revealed that overexpression of TMEM16A significantly increased transcription levels of these genes, which may explain why TMEM16A promotes cell proliferation in gliomas.…”
Section: A B a Bsupporting
confidence: 50%
“…Thus although Bax deletion does not directly model a genetic change seen in human medulloblastoma, the principle demonstrated by Bax deletion, that apoptosis is required for treatment sensitivity, remains highly relevant. Moreover, this principle may be generalizable to other cancers, where inactivating frameshift mutations in Bax have been identified, including human colon cancer, gastric cancer and high grade glioma [38–41]. Our data indicate that any mutation or post-translational event that impairs the internal apoptotic pathway can confer treatment resistance.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, pH-dependent impairment of cyclin D1 degradation could result from mutations in the naturally occurring glioma cell lines [34]. However, mutations in the structural gene of cyclin D1 in glioblastomas are very rare events [35], while overexpression of cyclin D1 is reported in more than 50% of astrocytic tumors [36].…”
Section: Discussionmentioning
confidence: 99%